Effectiveness analyses may underestimate protection of infants after group C meningococcal immunization - Vu, D; Kelly, D; Heath, P; McCarthy, N; Pollard, A; Granoff, D (University of Chicago Press, 2006)
Background. Group C meningococcal conjugate-vaccine effectiveness in the United Kingdom declines from ~90% in the first year to 0% between 1 and 4 years after immunization in infants immunized at 2, 3, and 4 months of age and to 61% in toddlers given a single dose. Confidence intervals are wide, and the extent of protection is uncertain. Methods. Serum samples were obtained from children 3-5 years of age who were participants in a preschool booster-vaccine trial. Serum bacterial activity was measured with human complement. Group C anticapsular antibody concentrations were measured by a radioantigen binding assay. Passive protection was analyzed in a infant rat bacteremia model. Results. Serum samples from UK children who had been immunized 2-3 years earlier as infants or toddlers had higher levels of radioantigen binding, bacterial activity, and passive protection than did historical control serum samples from unimmunized children (P<.05). A higher proportion of children immunized as infants had serum bactericidal activity tiers ≥ 1:4 (considered to be protective) than those immunized as toddlers (61% vs. 24%; P<.01), but there were no significant differences in the proportion of serum samples conferring passive protection (50% and 41%, respectively; P=.4). Conclusions. We found no evidence of lower immunity in children immunized as infants than as toddlers. On the basis of serum bactericidal activity and/or passive protection, 40%-50% of both age groups are protected at 2-3 years after immunization, which was significantly greater than in unimmunized historical controls (<5%).